Revealing the Dynamics of Hybrid Metal Halide Perovskite Formation via Multimodal In Situ Probes. (9th December 2019) - Song, Tze‐Bin; Yuan, Zhenghao; Mori, Megumi; Motiwala, Faizan; Segev, Gideon; Masquelier, Eloïse; Stan, Camelia V.; Slack, Jonathan L.; Tamura, Nobumichi; Sutter‐Fella, Carolin M.
Abstract: The exploration of the synthetic space of halide perovskites hinges on an enormous number of parameters requiring time‐consuming experimentation to decouple and optimize. Here, the formation of the prototype material CH3 NH3 PbI3 (MAPbI3 ) is investigated at different time and length scales using multimodal in situ measurements to monitor the evolution of crystalline phases, morphology, and photoluminescence as a function of the lead precursors. Kinetically fast formation of crystalline precursor phases already during the spin‐coat deposition is observed using lead iodide (PbI2 ) or lead chloride (PbCl2 ) routes. These precursor phases most likely template final MAPbI3 film morphology. In particular, the emergence of the "needle‐like" structure is shown to appear before film annealing. In situ photoluminescence measurements suggest nanoscale nucleation followed by rapid nuclei densification and growth. Using this multimodal in situ approach, different formation pathways can be identified either via precursor phases in the PbI2 and PbCl2 routes or direct perovskite formation from molecular building blocks as observed in the lead acetate (PbAc2 ) route. Correlation of in situ results with photovoltaic device performance demonstrates the power of in situ multimodal techniques, paves the way to a fast screening of synthetic parameters, and ultimately leads to controlled synthetic procedures that yield high‐efficiency devices. Abstract : The same unique properties that make lead halide perovskites remarkable solar energy conversion materials will also drive applications in other optoelectronic devices as more is learned about their formation. Insights are provided here by monitoring the in situ evolution of the crystal phase, morphology, and optoelectronic properties correlated to precursor chemistry.